Actual practice of standard treatment for pulmonary nontuberculous mycobacteriosis in Japan. (October 2019) - Morimoto, Kozo; Izumi, Kiyohiko; Ato, Manabu; Hasegawa, Naoki; Mitarai, Satoshi
Abstract: Introduction: The details of the practice of treating nontuberculous mycobacterial pulmonary disease (NTMPD) have not been studied in Japan. Methods: We studied a random sample of 2% (184) of the 9, 200 patients with incident NTM-PD in 2010 who received standard three-drug therapy for at least some of their treatment between 2010 and 2014. Results: The median duration of the standard treatment period was 248 days (IQR 56–540 days). Although 59% of the patients were treated with standard therapy for more than 6 months, only 41% were treated for 12 months. Fifty-three patients (29%) initiated treatment with substandard regimen, and 18 (34%) of those patients received treatment regimens that can lead to the development of macrolide resistance (MR)(CLR monotherapy or CLR + RIF). Furthermore, initially, 184 receiving the standard treatment, 49 patients (27%) eventually deviated from it, and 31 patients (63%) received regimens increasing the risk of developing MR. The sporadic administration of macrolide monotherapy was observed before and after the administration of the standard treatment for 50 patients (27.7%) and 41 patients (27.2%), respectively. Conclusions: Approximately 60% of the treated patients did not continue the standard regimen for more than 12 months and 42% were at risk for developing MR before and after receiving the standard treatment. It is important to educate physicians and patients about the correct and safe management of NTMPD. Highlights: Only 40% of the NTM-PD were treated >12 months with the standard regimens in Japan. Among the 27% of cases who changed the regimen, 63% had risk of macrolide resistance. Macrolides monotherapy were frequently prescribed even after registered as NTM-PD. Cessation of EMB due to side effect could be the cause of deviation from the standard. Countermeasures, including educational efforts and local guidelines, are essential.